The Handbook of contemporary semantic theory - Lappin, Shalom; Fox, Chris 1965- (Blackwell handbooks in linguistics, 2015)
"The second edition of The Handbook of Contemporary Semantic Theory presents a comprehensive introduction to cutting-edge research in contemporary theoretical and computational semantics. Features completely new content from the first edition of The Handbook of Contemporary Semantic Theory. Features contributions by leading semanticists, who introduce core areas of contemporary semantic research, while discussing current research. Suitable for graduate students for courses in semantic theory and for advanced researchers as an introduction to current theoretical work" -- Amazon.